Preparation method of porous ceramic, porous ceramic and atomizing core
The porous ceramic blanks are printed and sintered through three-dimensional photocuring forming technology, and the problems of uneven pore distribution and poor mechanical properties of existing porous ceramic materials are solved, and the preparation of porous ceramics with good porosity, controllable pore size and consistency are achieved.
Patent Information
- Application Number
- CN202311392488.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
The porous ceramic materials have poor pore distribution uniformity, poor mechanical properties and low production efficiency, making it difficult to prepare porous ceramics with high porosity, controllable pore size and good consistency.
Using three-dimensional photocuring forming technology, the raw material powder and photosensitive resin are mixed into a slurry, and the porous ceramic blank is printed, and porous ceramics with high porosity and controllable pore size are obtained through the sintering and glue discharge process.
The porous ceramics are prepared with high porosity, controllable pore size and good consistency, and the performance and production efficiency of the material are improved.
Smart Images

Figure CN119874402A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of porous ceramics, and in particular to a preparation method of porous ceramics, porous ceramics and an atomizing core. Background Art
[0002] Ceramic materials are a type of inorganic non-metallic materials made from natural or synthetic compounds through forming and high-temperature sintering. They are widely used. Porous ceramics are generally formed by high-temperature sintering of components such as aggregates, binders and pore-forming agents. They have a pore structure that is interconnected with each other and with the surface of the material. Porous ceramics have many applications in metallurgy, biology, energy, environmental protection and other fields due to their high porosity, stable chemical properties, large specific surface area, low volume density, low thermal conductivity and high temperature corrosion resistance.
[0003] Take the field of electronic cigarettes as an example: as an electronic product used to quit smoking or replace cigarettes, electronic cigarettes imitate the appearance of traditional cigarettes, do not produce tar, suspended particles and other harmful components in cigarettes, and will not bring the harm of secondary smoking or the problem of fire caused by improper handling of burning cigarette butts. At present, electronic cigarettes are mainly divided into two types, one is steam electronic cigarettes, which produce smoke by heating the smoke liquid; the other is heat-not-burn electronic cigarettes, which control the temperature to make the tobacco produce smoke but not burn. Steam electronic cigarettes use liquid smoke oil, which mainly contains ingredients such as glycerol (VG), propylene glycol (PG), nicotine and flavors.
[0004] Steam-type electronic cigarettes are mainly composed of an atomizer and a power supply component. The atomizer is the core device for producing atomized gas in electronic cigarettes, and its atomization effect determines the quality and taste of the smoke. At present, the core of the electronic cigarette atomizer is the atomizer core, on which a heating element is provided; the heating element is connected to the power supply component and generates heat when inhaled; the atomizer core is mainly made of two materials: the traditional fiber cotton atomizer core and the emerging ceramic atomizer core. Both are porous structures and play the role of guiding and dispersing the smoke oil. After the smoke oil is absorbed by the atomizer core, it is heated by the heating element to produce smoke aerosol, which manifests as the effect of atomization.
[0005] The cotton core is used as the atomization core of the electronic cigarette, and the smoke produced by the atomization has a good taste. However, when the atomization temperature is too high, the cotton core is prone to produce a burnt smell during use. The porous ceramic atomization core is an atomization core that has been rapidly developed and widely used in recent years. Because the porous ceramic has a porous structure, strong lipophilicity, uniform heating, and high temperature resistance, it is a good raw material for preparing the atomization core.
[0006] At present, the commonly used methods for preparing porous ceramic materials in industry mainly include adding pore-forming agent, organic foam impregnation, foaming, injection molding, particle stacking, etc. However, the above preparation methods all have their limitations. For example, the porous ceramic materials prepared by adding pore-forming agent have poor pore distribution uniformity, poor mechanical properties, and low production efficiency; the shape and density of products obtained by organic foam impregnation are difficult to control; the foaming method has high requirements for raw materials and the process conditions are difficult to control; the porosity of products obtained by particle stacking is low.
[0007] Therefore, how to prepare porous ceramic materials with high porosity, controllable pore size and good consistency is an urgent problem to be solved. Summary of the invention
[0008] In view of the above problems, the present application provides a method for preparing porous ceramics, and the prepared porous ceramics have high porosity, controllable pore size and good consistency.
[0009] This application solves its technical problems by adopting the following technical solutions: A method for preparing porous ceramics comprises the following steps: Mixing raw material powder with photosensitive resin into slurry, wherein the raw material powder includes aluminum oxide, silicon oxide and sintering aid magnesium oxide; Use stereolithography to print porous ceramic bodies; The porous ceramic green body is sintered and debinded to obtain porous ceramics.
[0010] Furthermore, the weight percentage of the photosensitive resin in the slurry is 10-40wt%.
[0011] Furthermore, the weight percentage of the sintering aid magnesium oxide in the raw material powder is 1-8wt%.
[0012] Furthermore, the average particle size of the sintering aid magnesium oxide is 15-100 μm.
[0013] Furthermore, the method of printing the porous ceramic body by stereolithography includes establishing a three-dimensional model of the porous ceramic, slicing the three-dimensional model and importing the model into a computer.
[0014] Furthermore, the sintering and debinding process includes sintering at 1400-1600° C. for 2-3 hours.
[0015] The present application also provides a porous ceramic prepared according to the above preparation method.
[0016] Furthermore, the porosity of the porous ceramic is 50-60%.
[0017] Furthermore, the average pore size of the porous ceramic is 10-25 μm.
[0018] The present application also provides an atomization core, comprising the above-mentioned porous ceramic.
[0019] Compared with the prior art, the preparation method of porous ceramics in the present application utilizes stereolithography technology to pre-establish a three-dimensional model of the porous ceramics, which is then sliced and printed layer by layer. The morphology of the prepared porous ceramics can be adjusted and controlled, and the prepared porous ceramics have high porosity, controllable pore size, and good consistency. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a physical picture of the porous ceramic prepared in the examples of the present application. Implementation
[0021] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described implementation methods are only part of the implementation methods of the present application, rather than all the implementation methods. Based on the implementation methods in the present application, all other implementation methods obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0022] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0023] The electronic cigarette includes an atomizer assembly and a power supply assembly. The atomizer assembly includes a liquid storage chamber for storing liquid (such as tobacco oil) and an atomizer core for absorbing the liquid in the liquid storage chamber and atomizing the liquid. Generally, the atomizer core includes a porous ceramic substrate and a heating element. The porous ceramic substrate is used to absorb the liquid in the liquid storage chamber, and the heating element is used to atomize the liquid absorbed by the porous ceramic substrate. The porous ceramic substrate has a liquid inlet surface, which is close to the outlet of the liquid storage chamber. During atomization, after the liquid in the liquid storage chamber flows out from the outlet of the liquid storage chamber, it enters the interior of the porous ceramic substrate through the liquid inlet surface of the porous ceramic substrate, and is heated by the heating element so that the liquid flowing out of the liquid storage chamber is atomized for inhalation.
[0024] The preparation method of the porous ceramics in the present application is described below.
[0025] A method for preparing porous ceramics comprises the following steps: mixing raw material powders with photosensitive resin into slurry, wherein the raw material powders include aluminum oxide, silicon oxide and a sintering aid magnesium oxide; printing a porous ceramic body by using stereolithography technology; and sintering and debinding the porous ceramic body to obtain the porous ceramic.
[0026] Specifically, the raw material powder includes the main components of aluminum oxide and silicon oxide, and the porous ceramics obtained therefrom have the characteristics of high strength, high hardness, wear resistance, corrosion resistance, high temperature resistance and good insulation, and are very suitable for the atomization core of electronic cigarettes. In addition, photosensitive resin is a liquid photocurable resin, or UV resin (glue), which is mainly composed of polymer monomers and prepolymers, to which light (ultraviolet light) initiator (photosensitizer) is added. When irradiated with ultraviolet light of a certain wavelength (250-300nm), a polymerization reaction will immediately occur to complete the solidification conversion. In the slurry formed by mixing the raw material powder and the photosensitive resin, the weight percentage of the photosensitive resin is 10-40wt%, for example, 10wt%, 20wt%, 30wt% or 40wt%.
[0027] The raw material powder also contains a sintering aid, which is a substance added during the ceramic sintering process to promote sintering densification. The sintering aid can be an oxide or a non-oxide; in the process of heating to a high temperature to combine the ceramic material together, the ceramic particles will undergo physical and chemical changes to form a dense ceramic material with a specific structure and properties. The addition of sintering aids in this process can promote these changes, help the ceramic particles to be more tightly combined, and form a denser material. By using sintering aids, the sintering process can be controlled and the performance and stability of the ceramic material can be improved. Magnesium oxide as a sintering aid has the following characteristics in the ceramic sintering process: (1) Lowering the sintering temperature: Magnesium oxide can promote diffusion and chemical reactions between ceramic particles, so that the ceramic material can be densified at a lower temperature. (2) Inhibiting grain growth: Magnesium oxide can effectively inhibit grain growth and help obtain ceramic materials with a fine-grained structure. By controlling the grain size, the mechanical properties and thermal stability of the ceramic can be improved. (3) Improving density: The addition of magnesium oxide can promote the densification of ceramic materials. It can accelerate grain boundary diffusion, refine grains, and inhibit the rapid movement of grain boundaries, so that pores are discharged more completely and ceramics are denser. However, it should be noted that adding an appropriate amount of magnesium oxide as a sintering aid is key. Excessive magnesium oxide may cause the performance of ceramic materials to deteriorate. The weight percentage of the sintering aid magnesium oxide in the raw material powder of the present application is 1-8wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt% or 8wt%. At the same time, the average particle size of the sintering aid magnesium oxide is selected to be 15-100μm, for example, 15μm, 20μm, 40μm, 55μm, 70μm, 80μm, 90μm, 95μm or 100μm.
[0028] Stereolithography (SLA) is a rapid prototyping process that uses ultraviolet lasers to precisely cure cross-sections of photopolymers, transforming them from fluid to solid. The technology is a type of 3D printing technology invented by Chuck Hull, co-founder and CTO of 3D Systems in the 1980s. In the stereolithography process, liquid photosensitive resin is contained in a tank; under ultraviolet light, these resins are cured. The work platform is located below the liquid surface, and the focused laser beam or ultraviolet light spot scans the liquid surface from point to line and from line to surface point by point according to computer instructions; the photosensitive resin liquid is cured in the scanned area, while the unscanned area remains liquid resin. When a layer is scanned, the lifting platform descends a layer thickness, covers it with a layer of liquid photosensitive resin, and scans the second layer again; the newly cured layer is firmly bonded to the previous layer, and this is repeated until the entire three-dimensional part is completed. Stereolithography is often used in processes that require highly shaped, matched and assembled parts. The tolerance of the parts is usually less than 0.05 mm, and it can provide the smoothest surface finish of all additive manufacturing processes. Stereolithography has a speed advantage when making various functional prototypes or rapid manufacturing castings.
[0029] When the present application uses stereolithography to print a porous ceramic body, it includes first establishing a three-dimensional model of the porous ceramic of the desired shape according to actual needs, then slicing the three-dimensional model and importing it to generate computer instructions, and finally printing a porous ceramic body with a certain shape.
[0030] The specific process of sintering and debinding in the present application is: put a porous ceramic body with a certain shape into a debinding furnace, heat it to 1400-1600°C at a certain rate, sinter it for 2-3 hours, then cool it to room temperature, open the furnace and take out the parts.
[0031] Through the above preparation method, the present application can prepare porous ceramics with step and groove shapes, a specific example of which is shown in the attached Figure 1 The present application uses a vernier caliper to measure the macroscopic size of the porous ceramic to verify whether the design requirements of size and shape are met.
[0032] The pore size of the porous ceramic is tested and photographed using an electron microscope scanner, and then the pore size of the porous material in the photograph is analyzed using finite element analysis software. The size parameter of the average pore size in the porous ceramic three-dimensional model can be adjusted according to different needs, for example, 10μm, 12μm, 15μm, 20μm, 23μm or 25μm. The determination of the above average pore size is based on the many years of experience of the inventor of this application, and comprehensively considers the balance between the oil conduction performance and the oil locking performance of the porous ceramic.
[0033] The porosity test of porous ceramics refers to "GB / T 1966-1996 Test method for apparent porosity and capacity of porous ceramics", for example, using the accurate MAY-Entris 120-D80V2 porosity analyzer for measurement; similarly, the porosity parameters in the porous ceramic three-dimensional model can be adjusted according to different needs, such as 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59% or 60%.
[0034] The compressive strength of the prepared porous ceramics was also tested. The test method referred to "GB / T 1964-1996 Porous Ceramics Compression Strength Test Method". The test contact area was 2mm×2mm, and the compressive strength of each surface needed to meet the requirement of being greater than 80N.
[0035] The present application also provides an atomizer core, comprising the above Figure 1 The porous ceramic of the shape shown is used as the substrate. Usually, the bottom surface of the porous ceramic substrate will be coated with a heating element, and the preparation of the atomizer core is completed. A specific preparation process is given below: a semi-automatic printer, a 200-mesh screen and a nickel-chromium conductive paste are used to print a conductive film (i.e., a heating element) on the bottom surface of the prepared porous ceramic, and the resistance of the printed conductive film is set to 1Ω.
[0036] The porous ceramic matrix has stable chemical properties, will not chemically react with the smoke liquid, can withstand high temperatures, and is an insulator, so it will not be electrically connected to the conductive film formed thereon to cause problems such as short circuits.
[0037] The present application will be further described below in conjunction with specific embodiments and drawings.
[0038] Example: Preparation method of porous ceramics Alumina, silicon oxide and sintering aid magnesium oxide are weighed and mixed into a raw material powder, wherein the weight percentage of the sintering aid magnesium oxide is 8wt% and the average particle size of the sintering aid magnesium oxide is 55μm.
[0039] The raw material powder is mixed with epoxy photosensitive resin to form a slurry, wherein the weight percentage of the epoxy photosensitive resin is 40wt%.
[0040] A three-dimensional model of the porous ceramic to be prepared is established, and then the three-dimensional model is sliced and imported into the generated computer instructions, and a porous ceramic body with a certain shape is printed using stereolithography technology.
[0041] The porous ceramic body is placed in a binder removal furnace and heated to 1600°C at a certain rate, kept at this temperature for 3 hours, then cooled to room temperature and the furnace is opened to take out the body.
[0042] like Figure 1As shown in FIG. 1 , it is a physical picture of the porous ceramic prepared in the embodiment. It can be seen from the figure that steps extend from both sides of the porous ceramic, and the porous ceramic also has a groove.
[0043] It is actually measured that the compressive strength of each surface of the porous ceramic is greater than 80N, the porosity is 59%, and the average pore size is 19μm.
[0044] The present application adopts stereolithography forming technology, which can flexibly adjust the morphology of the prepared porous ceramics, and the prepared porous ceramics have high porosity, controllable pore size and good consistency.
[0045] The above embodiments are merely examples for clearly illustrating the present application, and are not intended to be a complete limitation on the implementation methods. A person skilled in the art may make other variations based on the above descriptions, and it is not possible or necessary to provide examples for all implementation methods, but the obvious variations derived therefrom are still within the scope of protection of the present application.
Claims
1. A method for preparing porous ceramics, characterized in that: The steps include: Mixing raw material powder with photosensitive resin into slurry, wherein the raw material powder includes aluminum oxide, silicon oxide and sintering aid magnesium oxide; Use stereolithography to print porous ceramic bodies; The porous ceramic green body is sintered and debinded to obtain porous ceramics.
2. The method for preparing the porous ceramic according to claim 1, characterized in that: The weight percentage of the photosensitive resin in the slurry is 10-40wt%.
3. The method for preparing the porous ceramic according to claim 1, characterized in that: The weight percentage of magnesium oxide, a sintering aid, in the raw material powder is 1-8wt%.
4. The method for preparing porous ceramics according to claim 1, characterized in that: The average particle size of the sintering aid magnesium oxide is 15-100 μm.
5. The method for preparing a porous ceramic according to any one of claims 1 to 4, characterized in that: The method of printing the porous ceramic body by stereolithography includes establishing a three-dimensional model of the porous ceramic, slicing the three-dimensional model and importing the model into a computer.
6. The method for preparing a porous ceramic according to any one of claims 1 to 4, characterized in that: The debinding sintering process includes sintering at 1400-1600° C. for 2-3 hours.
7. A porous ceramic, characterized in that: The porous ceramic is prepared according to the method for preparing the porous ceramic according to any one of claims 1 to 6.
8. The porous ceramic according to claim 7, characterized in that: The porosity of the porous ceramic is 50-60%.
9. The porous ceramic according to claim 7, characterized in that: The average pore size of the porous ceramic is 10-25 μm.
10. An atomizer core, characterized in that: The atomizing core comprises the porous ceramic according to any one of claims 7 to 9.